The role of nickel and nickel-mediated reactive oxygen species in the mechanism of nickel carcinogenesis. - Huang, X (1994)
Increasing evidence demonstrates the reactive oxygen species (ROS) are implicated in metal carcinogenesis. Exposure of cultured Chinese hamster ovary (CHO) cells to several nickel compounds, i.e. NiS, Ni3S2, NiO (black and green), and NiCl2 has been shown to increase oxidation of 2',7-dichlorofluorescein to the fluorescent 2',7-dichlorofluorescein (DCF), suggesting that nickel compounds increased the concentration of oxidants in CHO cells. This fluorescence can be attenuated by addition of exogenous catalase to the extracellular media, indicating that H2O2 is one of the formed oxidants in this system. Fluorimetric measurements of chromogens following thiobarbituric acid reaction showed that nickel compounds also induce lipid peroxidation with a decreasing potency NiS, Ni3S2 > black NiO > green NiO > NiCl2. These results suggest that lipid hydroperoxides may also be produced through the action of nickel in intact cells. MgCl2, an antagonist of Ni-induced DNA strand breaks and cell transformation, has no effect on the formation of DCF fluorescence induced in CHO cells by nickel. The results suggest that nickel is an active inducer of ROS in intact mammalian cells and that the molecular mechanism of nickel carcinogenesis may involve multiple steps of nickel-mediated ROS.